ECONOMETRIC MODEL OF FACTORS INFLUENCING THE CHANGE IN COMPANY CAPITALIZATION - Babich-Gaury, A.V.; Babich , V. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article considers the applied aspect of using econometric analysis methods of time series to assess factors that directly affect the value of a company. The basic mathematical apparatus is used to test hypotheses and build econometric models which are used in time series analysis. By determining the factors that affect the level of capitalization, hypotheses about the significance of these estimates are assessed and the level of the impact and consequence on key performance indicator as the company's net revenue is determined. Currently the global economy demonstrates high inflation rates in south and west parts of the world. Therefore, the author identifies the dependence that links the inflation rate and the level of turnover. A regression model of the relationship between changes in revenue and the level of return on invested capital is considered. Any investor seeks to increase the value of the company, so it is important to assess the main factors that affect this value.